PENGARUH IRADIASI SINAR GAMMA TERHADAP VARIASI PERTUMBUHAN ANGGREK Brachypeza indusiata (Reichb.f) Garay SECARA IN VITRO - Wardhani, Maria Utami Dewi; Puspitaningtyas, Dwi Murti; Dinarti, Diny (Buletin Kebun Raya, 2007)
A research was carried out in Orchid Laboratory of Bogor Botanical Gardens to observe the effect of gamma ray irradiation on the growth variation of Brachypezo indusiata (Reichb.f) Garray and suitable culture medium for propagating the plant. The research was arranged in a factorial experiment with a Completely Randomized Design. The first factor was gamma ray irradiation on protocorm-likeÂbodies (plb) of germinated seeds of B. indusiata in which four levels of irradiation was applied, i.e. 0, 10, 20, and 30 Gy. The second factor was the use of two different culture media, i.e. Vacin & Went medium supplemented with either banana pulp or a mixture of tomato and sprout bean as the essential organic compound of the medium. The result showed that the irradiation treatment improved the survival of B. indusiata explants, most significantly at 20 Gy level of irradiation, and could modify the growth of the resulted plantlets by reducing the height of the plant and the length and width of the leaves. The higher the level of irradiation the smaller the plantlets produced. Meanwhile, the addition of organic compound derived from banana fruit into the basal medium of Vacin & Went enhanced the growth of the plantlets better than that derived from a mixture of tomato fruit and bean sprout. However, there was no significant interaction effect detected between the irradiation treatments and the use of different culture media.